Minimum built form for maximum urban impact: exploring the minimum built form that generates the greatest urban impact through architecture of closed-loop material systems - Moreau, Daniel (School of Architecture, Planning and Geomatics, 2018)
Current top-down city planning strategies implement abstract ideas and impose them on a society while neglecting a crucial sense of public voice and inclusion (Krause, 2011). Through exploring ideas of community ownership of space and flexibility of social inhabitation, the design dissertation aims to understand the minimum built form that generates the greatest urban impact through architecture of closed-loop material systems. The inquiry focuses on urban upgrade that is low in embodied energy and holistic in its processes and implementation, where the social side of community participation is overlapped with technical explorations of material re-use and local procurement that promotes inclusive architecture. The use of low-tech materials requires high amounts of labour, which generates a positive state of community buy-in and inclusion both qualitatively (dignity and ownership) and qualitatively (Job creation). The design dissertation demonstrates how a relatively small building can make massive improvements in activation of site and precinct, being catalytic with community participation and urban upgrade of a rich, authentic nature. The aspiration of this design research is to generate a speculative design framework and set of experimental design details that are useful to local municipalities, planners, urban designers, architects and NGO's that are interested in developing sustainable models for upgrade in under-resourced neighbourhoods of the Cape Town townships. With enough planning and unique tailoring of the building contract, procurement, project management and community involvement, these new typologies can offer more integrity than current and conventional builds. Unique teams require brave and unconventional practices that step out of the rigid comfort zone architects call the industry.